Evaluasi Aplikasi Sistem Informasi Manajemen Puskesmas (SIMPUS) di Puskesmas Tanjung Puri Kabupaten Sintang Tahun 2024 - Sardi, Aditiya (LANCAH: Jurnal Inovasi dan Tren, 2024)
To support the implementation of medical record and health information services at the puskesmas, a system called the puskesmas management information system is used. is an arrangement that provides information to assist the decision-making process in implementing puskesmas management in achieving targets activities. Objective: To know the evaluation of the implementation of the puskesmas management information system. Research Method: The research method used is a qualitative method with a descriptive approach. Data collection techniques used are interviews, observation, and documentation. Research Results: The use of System Infromation puskesmas has not been fully effective because the information produced is not relevant to the facts that occur in the field. The inhibiting factors in implementing System Infromation puskesmas are the behavior of officers, human resources, public facilities, and software systems. Conclusion: System Infromation puskesmas implementation has not run optimally. Suggestion: Conduct training on System Infromation puskesmas and seek a management function for the Head of the Puskesmas in the form of a supervisory function for officers to be more disciplined and timely in collecting data for the officer responsible for System Infromation puskesmas at the puskesmas.